DEGARELIX ROLE AND PLACE IN THE COMBINED TREATMENT OF PATIENTS WITH PROSTATE CANCER IN COMBINATION WITH CONCURRENT RADIOTHERAPY - A. Y. Pavlov; R. A. Gafanov; S. V. Fastovets; A. D. Tsybulsky; T. K. Isaev (Сибирский онкологический журнал)
Application Degarelix ADT patients who underwent combined radiotherapy, already on the first results showed the high efficiency and low toxicity. For patients with localized prostate cancer with intermediate factors and a poor prognosis, as well as for patients with locally advanced disease, we recommend a hormone antagonists of gonadotropin-releasing hormone (GnRH) Firmagon (Degarelix) not only during concomitant radiation therapy, but also as neoadjuvant and adjuvant treatment.